Effect of psyllium husk on low anterior resection syndrome after rectal cancer surgery—a pilot prospective cohort study - Holte, Silje Stensholt; Avaliani, Natalia; Hoff, Geir; Kazaryan, Airazat M.; Jaioun, Keson; Lauzikas, Giedrius; Schultz, Johannes Kurt (Frontiers in Surgery, 2025)
IntroductionLow anterior resection syndrome (LARS) is a frequent, undesired consequence of rectal cancer surgery. Psyllium husk has been suggested as a nutritional supplement in the management of LARS, but without trial-based evidence of its effect. In preparation of a randomized clinical trial, this pilot study aimed to estimate the effect of Psyllium husk in patients with LARS, determining the treatment duration required to observe the effect and assess patient compliance.MethodsThis single arm phase II study included patients with LARS score >20 ten months or more after rectal resection. Patients who consented to participate were given 3.66 g Psyllium husk fiber twice daily for 56 days. The primary endpoint was severity of bowel dysfunction using the LARS score. The secondary endpoint was quality of life (QoL) using EQ-VAS score in the EQ-5D-5L questionnaire. A reduction of 7 points in LARS score was considered clinically relevant. Questionnaires and scores were collected on paper day 0 (baseline), day 28 and day 56.Results22 patients were assigned to the intervention and included in the analysis. The average age was 65.3 (SD 10.4), the average LARS score at baseline was 35,7 (SD 3.5), four patients had received radiotherapy. The proportion of patients with a LARS score reduction of 7 points or more compared to baseline was 50.0% at day 28 (11/22) and 50.0% at day 56 (10/20). The mean reduction in LARS scores from baseline to 8 weeks of treatment was 7.7 points. At day 28, the proportion of patients with a QoL score (EQ-VAS score) increase of 10 points or more was 36.4% (8/22), increasing to 60.0% (12/20) by day 56. Two patients dropped out after 4 weeks of treatment, one due to taste and consistency of the supplement and one due to inconsistently beneficial effect.ConclusionsPsyllium husk appears to clinically significantly improve both bowel dysfunction and QoL in rectal cancer patients suffering from LARS. This study highlights the need for further systematic research, and provides a strong basis for a well-designed RCT.